Ecotourism, Religious Tourism, and Religious Naturalism - Yoder, Scot D. (Journal for the study of religion, nature and culture, 2017)
Much can be learned about both ecotourism and religious naturalism by bringing the two into conversation through the concept of religious tourism. In Part One I argue that ecotourism can be perceived as religious tourism based on the claim that the concept of nature that serves as a basis for ecotourism is also used in the process of making nature sacred'. I use the example of tourism in Monte Verde, Costa Rica to show how nature can be made sacred in ecotourism and end the section by suggesting what we might gain from looking at ecotourism in this way. In Part Two I describe religious naturalism, then explore how thinking of ecotourism as religious tourism might address concerns regarding religious practice, conceptions of nature, and the apparent inability of religious naturalism's non-anthropocentric ethic to deal with issues of environmental racism and social justice.